2005
DOI: 10.1248/bpb.28.1117
|View full text |Cite
|
Sign up to set email alerts
|

Antitubercular Activity and Inhibitory Effect on Epstein-Barr Virus Activation of Sterols and Polyisoprenepolyols from an Edible Mushroom, Hypsizigus marmoreus

Abstract: Hypsizigus marmoreus (Buna-shimeji) has recently become a popular edible mushroom in Asia, and has been cultivated by culture methods such as bottle culture and bag-culture. It has been reported to exhibit many biological activities such as anti-tumor, 1,2) antioxidant, 1) and antiproliferative activity. 3) Several homologous polyisoprenepolyols named hypsiziprenols have recently been characterized in this mushroom. 4) Hypsiziprenols are the possible biosynthetic precursors of gymnopilins, bitter principles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Additional biological activities of ergosterol peroxide have been reported, i.e., antioxidant (Kim et al 1999), antimycobacterial (Cantrell et al 1999;Akihisa et al 2005;Duarte et al 2007), antiplasmodial (Kuria et al 2002), leishmanicidal activity (Correa et al 2006), antiinflammatory (Yasukawa et al 1996;Gao et al 2007;Kobori et al 2007), immunosuppressive (Kuo et al 2003), anti-atherosclerosis (Kim et al 2005) and aldose-reductase inhibitory activity (Lee et al 2006). Aside from the reported biological activities, we found that ergosterol peroxide had an effect on in vitro insect cells and an insecticidal activity against 3rd instar S. litura larvae via topical application.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Additional biological activities of ergosterol peroxide have been reported, i.e., antioxidant (Kim et al 1999), antimycobacterial (Cantrell et al 1999;Akihisa et al 2005;Duarte et al 2007), antiplasmodial (Kuria et al 2002), leishmanicidal activity (Correa et al 2006), antiinflammatory (Yasukawa et al 1996;Gao et al 2007;Kobori et al 2007), immunosuppressive (Kuo et al 2003), anti-atherosclerosis (Kim et al 2005) and aldose-reductase inhibitory activity (Lee et al 2006). Aside from the reported biological activities, we found that ergosterol peroxide had an effect on in vitro insect cells and an insecticidal activity against 3rd instar S. litura larvae via topical application.…”
Section: Discussionsupporting
confidence: 55%
“…and Penicillium sp. (Nemec et al 1997;Kuo et al 2005), mushrooms (Mizushina et al 1998;Kim et al 1999;Li et al 2004;Akihisa et al 2005;Gao et al 2007), marine organisms (Gunatilaka et al 1981), lichens (Rubio et al 2005), algae (Sheffer et al 1986;Yasukawa et al 1996) and plants (Kuria et al 2002;Kim et al 2005;Macias et al 2006). This is the first report of ergosterol peroxide isolation from N. rileyi.…”
Section: Discussionmentioning
confidence: 80%
“…-The MeOH extract of the fruiting bodies of G. lucidum was purified by column chromatography on silica gel followed by preparative reversephase HPLC, yielding four known lucidenic acid derivatives, lucidenic acid B (3) [8], methyl lucidenate C (4) [9], lucidenic acid F (9) [6] [10], and lucidenic acid N (10) [11], six known ganoderic acids and related compounds, ganoderic acid A (20) [12], ganoderic acid C 1 (21) [10], ganoderic acid C 2 (22) [10], ganoderic acid DM (24) [13], ganodermanondiol (21) [14], and ganolactone (27) [15], as well as six known sterols, fungisterol (28) [16], 5,6-dihydroergosterol (29) [16], ergosterol (30) [17], ergosterol peroxide (31) [17], 9(11)-dehydroergosterol peroxide (32) [18], and demethylincisterol A 3 (33) [19] [20]. These compounds were identified by comparison of the spectroscopic data with those reported in the literature.…”
mentioning
confidence: 99%
“…Two other derivatives of vulpinic acid, (6) and 7, obtained from 5 by semi-synthetic modifications showed very weak antitubercular activity (MIC of 100 μg/mL) [10]. Recently, several secondary metabolites isolated from the edible mushroom Hypsizigus marmoreus have been shown to exhibit antitubercular activity and an inhibitory effect on tumor promotion [12]. Hypsizigus marmoreus (Peck) Bigel., known in Asia under a common name buna-shimeji, has been reported to exhibit many biological activities such as anti-tumor, antioxidant and antiproliferative activity.…”
mentioning
confidence: 99%
“…Six sterols (9)(10)(11)(12)(13)(14) and two polyisoprenepolyols (15,19) showed an MIC in the range of 1-51 μg/mL, while the other compounds (8, 16-18, 20-22) were inactive (MIC > 128 μg/mL). Ergosterol peroxide (9) and cerevisterol (10) showed the highest antitubercular potency with MIC values of 1 μg/mL and 6 μg/mL respectively, as compared to a positive control (rifampin MIC 0.25 μg/mL).…”
mentioning
confidence: 99%